DOI: 10.14264/uql.2019.182
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of paediatric hot beverage scalds

Abstract: Hot beverage scalds are a painful and, unfortunately, common burn injury in children accounting for 1 in 5 of all childhood burns treated. Despite the high incidence, physical suffering, potential psychological issues, and significant financial costs to the healthcare system, there is a paucity of research and initiatives aimed at preventing hot beverage scalds (HBS). The aim of this research is to provide a better understanding of HBS injuries and develop an intervention aimed at preventing them.The research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…To use these methods, it is important to compare the effect of different rearing temperatures with water at different temperatures to specify which stimulus maximizes BAT function [ 75 ]. Moreover, warm water administration might cause adverse effects to newborns when the temperature of the water is too high, causing burns and scalds, particularly in human infants [ 181 ]. In addition, although there are no studies in animals, in humans it has been reported that drinking warm (50–52 °C) or cold fluids alters evaporative heat loss by sweating and muscle activation, a change that can occur within one minute after warm water ingestion and might represent an increase in heat loss by sweating [ 182 ].…”
Section: Extrinsic Factors Involvedmentioning
confidence: 99%
“…To use these methods, it is important to compare the effect of different rearing temperatures with water at different temperatures to specify which stimulus maximizes BAT function [ 75 ]. Moreover, warm water administration might cause adverse effects to newborns when the temperature of the water is too high, causing burns and scalds, particularly in human infants [ 181 ]. In addition, although there are no studies in animals, in humans it has been reported that drinking warm (50–52 °C) or cold fluids alters evaporative heat loss by sweating and muscle activation, a change that can occur within one minute after warm water ingestion and might represent an increase in heat loss by sweating [ 182 ].…”
Section: Extrinsic Factors Involvedmentioning
confidence: 99%